2002
DOI: 10.1161/01.str.0000014508.65367.8f
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydia pneumoniae Serology Is Associated With Thrombosis-Related but Not With Plaque-Related Microembolization During Carotid Endarterectomy

Abstract: Background and Purpose-Chlamydia pneumoniae has repeatedly been associated with atherosclerotic disease. Our study was designed to clarify whether this association is based on C pneumoniae-induced transformation of a stable into an unstable atherosclerotic plaque or on stimulation of hypercoagulability leading to increased thrombotic arterial occlusions by C pneumoniae infection. Transcranial Doppler ultrasonographic monitoring of the middle cerebral artery during carotid endarterectomy offers the opportunity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
3

Year Published

2003
2003
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 60 publications
2
13
0
3
Order By: Relevance
“…Such authors remember that the single positivity for pneumoniae is not enough to explain the event of the cerebrovascular process, and conclude that the bacteria has an insignificant role in converting a atherosclerotic plaque into the symptomatic state 21 . In an analysis performed with the serum level of IgA and IgG in the carotid plaque withdrawn by endarterectomy, Vainas et al 22 conclude, in a similar way to our casuistic, that pneumoniae is not related to plaque destabilization. Such authors 22 state that this infectious agent would be related to atherosclerotic phenomena, probably in the first stages of its development, but would not have any role in plaque destabilization.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Such authors remember that the single positivity for pneumoniae is not enough to explain the event of the cerebrovascular process, and conclude that the bacteria has an insignificant role in converting a atherosclerotic plaque into the symptomatic state 21 . In an analysis performed with the serum level of IgA and IgG in the carotid plaque withdrawn by endarterectomy, Vainas et al 22 conclude, in a similar way to our casuistic, that pneumoniae is not related to plaque destabilization. Such authors 22 state that this infectious agent would be related to atherosclerotic phenomena, probably in the first stages of its development, but would not have any role in plaque destabilization.…”
Section: Discussionsupporting
confidence: 83%
“…In an analysis performed with the serum level of IgA and IgG in the carotid plaque withdrawn by endarterectomy, Vainas et al 22 conclude, in a similar way to our casuistic, that pneumoniae is not related to plaque destabilization. Such authors 22 state that this infectious agent would be related to atherosclerotic phenomena, probably in the first stages of its development, but would not have any role in plaque destabilization. In a recent study, by means of the analysis of carotid plaques obtained through endarterectomy in patients with atherothrombotic stroke, no relation to pneumoniae was detected 12 .…”
Section: Discussionsupporting
confidence: 83%
“…80 Chlamydial heat shock protein-60 induced the production of TNF-␣ and matrix-degrading metalloproteinases by plaque macrophages, mechanisms that may contribute to plaque rupture and thrombosis. 64 Clinical data support that the presence of C pneumoniae in carotid stenoses increases local thrombogenicity and the risk of infarction, 62,81 but not all results favor this hypothesis. 65 Some [82][83][84][85] but not all 86,87 seroepidemiological studies reported an association between past C pneumoniae infection and asymptomatic carotid atherosclerosis or increased intimamedia thickness.…”
Section: Continuous Inflammation In Matured Atherosclerotic Plaquesmentioning
confidence: 99%
“…However, Ieven et al [74] did not observe any differences in the IgG antibodies against chlamydia assessed by immunofluorescence in 106 patients with coronary artery disease and 112 healthy controls, probably due to cross-reactions with other bacteria. On the other hand, Vainas et al [75] described an association between IgA seropositivity and intraoperative thromboembolism in plaques considered histologically stable suggesting that infection by chlamydia can also have a thrombogenic effect in atherosclerosis.…”
Section: Serological Markersmentioning
confidence: 99%
“…On the other hand, there is evidence suggesting that thinning of the fibrous cover, the presence of "soft" content or of ulceration give instability to the plaque [103,104], and that the proximity of necrotic regions, specifically if associated to infiltration of macrophages, predispose the patient to clinical events [105]. Moreover, both in models utilizing surface ultrasonography and in more recent studies with computed reconstruction or intravascular ultrasonography, low echogenicity images have been related to necrotic or hemorrhagic content of the plaque [106][107][108], and the degree of calcification is considered to be inversely proportional to the stability of the lesions [75]. It is well known that, for any hemodynamically significant stenosis, patients with less echogenic plaques present with a higher incidence of cerebral infarction.…”
Section: Morphological Aspects Of Atheroma In Carotid Artery Diseasementioning
confidence: 99%